Polarimetry in the outskirts of NGC 6611 - Orsatti, Ana María (2006)
We present new polarimetric UBVRI observations of 25 stars in the direction of the halo of NGC 6611, the rich stellar open cluster embedded in an ionized hydrogen complex (M16). Our plan is to characterize the interstellar material (ISM) associated with halo stars in order to make a comparison with the ISM dusty core characteristics that resulted from a previous investigation by the same authors. Of the halo stars, 47% (8 out of 17) show indications of intrinsic polarization in their light, similar to what was found for core stars (50%). We have identified the presence of nearby dust clouds located on the Local arm that produce a mean polarization of about 1%; a value λmax = 0.61 ± 0.07 μm, which is slightly larger than that of the average ISM; and a mean direction of the polarization vectors of θV = 81.°9 ± 1.°8. The ISM associated with the halo region has λmax similar to the general interstellar medium (0.55 ± 0.07 μm). The observed polarizations show a gradual increase from halo (Pmax = 1.93% ± 0.3%) to core (Pmax = 3.19% ± 0.63%). Position angles of the e-vector for both groups are generally similar, but there exists a slight difference in mean direction between them that is within the errors. We have also found that the halo stars are possibly represented by Whittet & van Breda's relationship, while in the cluster's core the dust does not fulfill the above-mentioned relationship. As a conclusion, we cannot find any clear difference between core and halo dust characteristics, with the exception of λmax, which may suggest a change in dust size.